THE FINANCIAL DISTRESS STRATEGY TO PREDICT THE BANKRUPTCY OF SOEs MANUFACTURING CLUSTERS DURING THE COVID-19 PANDEMIC FOR THE FISCAL YEAR 2020-2021 - Nyaman, Nyaman; Samsi, Nur (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
This study aims to test the accounting-based bankruptcy prediction model with real data on Growth Opportunities and Financial Performance. The research focused on one of the state-owned enterprises, namely PT. Barata Indonesia, which is currently experiencing poor performance in meeting its loan obligations due to the impact of the COVID-19 pandemic. Bankruptcy prediction is done using Springate (S-score), Zmijewski (X-score) and Grover (G-score) methods. The results showed that the Springate and Grover method showed that PT. Barata Indonesia is experiencing financial distress, while the Zmijewski method shows the opposite.